ORGANOLEPTIC ANALYSIS OF EGG WHITE SUBSTITUTION ON ANCIFISH NUGGET (Stolephorus sp) - Kaliky, Nurainy (Asian Journal of Aquatic Sciences, 2022)
Nugget is one of the processed products from fish meat, whether fish is economically important or not. Nuggets are very popular with various circles of society because of their savory and delicious taste. Nuggets are made from fish meat and are believed to have a composition of nutritional value that is needed by the human body. This study aims to see the effect of adding egg whites to the organoleptic test of the nuggets produced and to see the level of preference of the panelists on the refined anchovy nuggets produced. The usefulness of this research is the diversification of processed fishery products that can be consumed by the community and has important economic value and it is hoped that the research results will be useful for the community about new sources of information regarding egg white substitution can produce anchovy nuggets (Stolephorus, sp) with good organoleptic tests. The method used is an experimental method. In this study, there were 2 treatments, namely there were two treatments A (egg white concentration) namely A1 = 50 g egg white, A2 = 100 g egg white A3 = 150 g egg white and treatment B ( heating temperature) namely B1 = 40 0C 15 minutes, B2 = 65 0C 20 minutes, B3 = 95 0C 30 minutes. In this study, subjective observations were made including color, texture, folding, and taste tests carried out by 15 panelists. The results showed that the administration of egg whites and heating at a temperature of 650C produced a good gel nugget color, due to a change in the color pigment. Egg whites can inhibit the softening of the gel because when heated, the value of the texture of the nugget becomes better. Meanwhile, the folding test value obtained was very high, namely 3.754, due to the fact that egg white inhibits serine proteinase so that the gelling strength increases.